PENGARUH STRES KERJA, SELF EFFICACY DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. MAHKOTA GROUP TBK - Jefri Pranata; Ahmad Fadli; Ah Rivai (Jurnal Mahkota Bisnis (Makbis), 2025)
This research aims to determine the influence of work stress, self-efficacy and work discipline on employee job satisfaction at PT. Mahkota Group Tbk. This research uses quantitative methods by collecting data through questionnaires. The population in the research was 69 employees who came from personal management at PT. Mahkota Group Tbk, while the researcher's determination technique used a saturated sample. Where the entire population is used as a sample or census method. The data sources in this research are primary data and secondary data, while the data analysis methods used in this research are multiple regression analysis and hypothesis testing. From the results of this research, it can be seen that the questionnaire item statement is declared valid because the value of rcount> rtable. Partially (one by one) it was found that the influence of the work stress variable (X1) had a positive and significant effect on employee job satisfaction (Y) where the work discipline variable had a value of tcount> ttable. Partially (one by one) it was found that the influence of the self-effcacy variable (X2) had a positive and significant effect on employee job satisfaction (Y) where the work discipline variable had a value of tcount> ttable. Partially (one by one) it was found that the influence of the work discipline variable (X3) had a positive and significant effect on employee job satisfaction (Y) where the work discipline variable had a value of tcount> ttable. and Overall (simultaneously) the influence of the work stress variable (X1), self ability (X2) and work discipline variable (X3) has a positive and significant effect on employee job satisfaction (Y) because the calculated Fcount for the work stress variable (X1), self-efficacy (X2) and work discipline variable (X3) > Ftable. The determination results obtained from work stress (X1), self-efficacy (X2) and work discipline (X3) can show a strong relationship to employee job satisfaction.